Analisis Perilaku Pustakawan Di Dinas Perpustakaan Dan Kearsipan Kota Pekanbaru - rizkia, ayu (Jurnal Tadwin, 2022)
The title of this research is an analysis of the behavior of librarians at the Pekanbaru City Library and Archives Service. The purpose of this study was to find out how the behavior of librarians at the Pekanbaru City Library and Archives Service in the field of service in the library. The method used is mixed research, which is a combination of quantitative and qualitative research, with a quantitative research sample of 100 users and a qualitative research sample of librarians who work in other fields of library service. Data collection techniques are questionnaires, interviews, observations, literature studies and documentation. The results of quantitative research show that the behavioral analysis of librarians at the Pekanbaru City Library and Archives Service is stated to be good with an average value in the range of 2.51 – 3.25 while qualitative research shows that the efforts of librarians in the services of the Pekanbaru City Library and Archives Service need to be improved due to the lack of librarian staff in the library service division, resulting in several obstacles including, the lack of accessibility of library services to users as a whole and the lack of access to information and knowledge of librarians in the field of library services.